Systemic sclerosis in Native Americans of the American Southwest - Emil, N. Suzanne; Vondenberg, Jaime A.; Waters, Yvonne M.; Muruganandam, Maheswari; Ariza‐Hutchinson, Angie; Patel, Rosemina A.; Nunez, Sharon E.; Gibb, James I.; McElwee, Matthew K.; Poole, Janet L.; O’Sullivan, Frank X.; Fields, Roderick A.; et al. (International journal of rheumatic diseases, 2022)
Objective Many indigenous non‐Caucasian populations, including Native Americans, have been reported to have higher rates, distinct clinical phenotypes, increased complications, and greater severity of systemic sclerosis (SSc). However, little is known of SSc specifically in Native Americans of the American Southwest. This study compared the clinical and serologic manifestations and outcomes of SSc in Native Americans and non‐Native Americans (non‐Natives) of this region. Methods This cross‐sectional retrospective study included 137 SSc patients (109 [80%] were non‐Native and 28 [20%] were Native Americans) followed over a mean of 11.5 ± 7.6 years. Participants were repetitively evaluated with medical history, physical examination, echocardiography, chest imaging, and serologic testing. Disease characteristics and outcomes were statistically compared between Native Americans and non‐Native patients. Results The estimated prevalence of SSc in Native Americans was 40.0 cases/100 000 vs 17.1 cases/100 000 for non‐Natives (odds ratio 2.34, 95% confidence interval [CI] 1.55‐3.55, P < .001). The cohorts were similar in terms age, age of onset, limited vs diffuse cutaneous SSc, telangiectasias, gastroesophageal reflux disease, Raynaud phenomenon, serologies, interstitial lung disease, pulmonary arterial hypertension, scleroderma renal crisis, cancer prevalence, and overall mortality (all P > .05). However, for Native Americans, mortality specifically from fatal infections was 3.94‐fold that of non‐Natives (hazard ratio 6.88, 95% CI 1.37‐34.64; P < .001). Conclusion In Native Americans of the American Southwest, SSc is increased in prevalence but is phenotypically similar to SSc in non‐Natives. However, mortality due specifically to infection is increased in Native Americans with SSc.